PERLINDUNGAN HUKUM TERHADAP PEREMPUAN KORBAN KEKERASAN DALAM RUMAH TANGGA - Galih Wiantaka, I Nyoman; Suarbha, I Wayan (Kertha Wicara : Journal Ilmu Hukum; Vol. 03, No. 03, Juli 2014)
Violence constituted within household, especially directed towards women, had occurred frequently. This matters raise due to several factors, namely gender factor. Basically, all forms of violence is an act of violation to human rights and crimes against humanity also a form of discrimination which needs to be eradicated soon in the near future. This issue had been regulated within the stipulation of Law No.23 of 2004 concerning Elimination of Household Violence. Tentang Penghapusan Kekerasan dalam Rumah Tangga. In order for that law to be meant as its goal, active participation of all legal enforcers as stake holders is essentially needed.
Keywords: legal protection, women, violence, discrimination